Prokrastinasi: Problem Manajemen Waktu Mahasiswa? - Siti Mulyanah (Journal of Information Systems and Management (JISMA), 2024)
The purpose of this research is to find out what factors influence academic procrastination in students and to create a measuring tool for academic procrastination. In this study report, a qualitative descriptive method was used by taking notes because the data source was obtained by listening to the oral narrative from the On Marissa's Mind YouTube channel entitled "Prorastination" which he explained. The results of this research explain that academic procrastination is influenced by various factors including time management, inability to concentrate and low awareness, fear and anxiety related to one's failure, and lack of confidence in one's abilities. The factor that really influences academic procrastination is time management. The aim of this research is to determine the relationship between time management and academic procrastination.